PENGARUH GAYA POTONG PEMBUBUTAN TERHADAP KEAUSAN PAHAT KARBIDA COATED PADA BENDA KERJA BAJA AISI 4340 - Rosehan Rosehan Rosehan (Jurnal Ilmiah Teknik Mesin POROS, 2018)
Cutting force and tool life is the important data in planning a machining process. The research is in order to describe about the influence of the cutting force to the tool wear on carbide coated cutting tools used the turning process of an alloy steel of AISI 4340. The research was conducted by observing the growth of tool wear on minutes 4.5, 9, 13.5, 18, 22.5 with the maximum value VB 0.3 mm, at the same time, the condition of other cutting such as the motion while the cutting, the depth and speed of the cutting movement was constant. The purpose of this experiment is to examine scientifically the influence cutting force to the growth of tool wear on carbide coated while the cutting process of alloy steel AISI 4340. The graphical method was used for the trial analysis, to see the cutting force comparison with the decrease of tool life of the carbide coated, and the correlation of the cutting movement with the cutting force. The mechanism decrease showed the adhesion decrease.